234 In utero heat stress alters the postnatal immune and metabolic response of growing pigs subjected to a lipopolysaccharide challenge. (30th November 2020) - Johnson, Jay S; Maskal, Jacob M; Duttlinger, Alan W; Kpodo, Kouassi R; McConn, Betty R; Byrd, Christopher; Richert, Brian T; Lay, Donald; Marchant-Forde, Jeremy; Lucy, Matthew; Safranski, Tim
Abstract: In utero heat stress (IUHS) reduces swine productivity and welfare but little is known about the long-term impact on immune function. The study objective was to determine the effects of IUHS on the immune and metabolic response of pigs subjected to an 8 h lipopolysaccharide (LPS) challenge during postnatal life. Twenty-four pregnant gilts were exposed to thermoneutral (TN; n = 12; 17.5 ± 2.1⁰C) or heat stress (HS; n = 12; cyclical 27°C-37°C) conditions from d 1 to 58 of gestation, and TN conditions from d 59 of gestation to farrowing. After farrowing, all piglets were housed under the same conditions. At 12 weeks post-farrowing, 16 IUHS and 16 in utero thermoneutral (IUTN) pigs were selected, balanced by sex and given an intravenous injection of LPS (2 µg/kg BW) or saline (SAL). Treatment combinations were: IUTN-SAL, IUTN-LPS, IUHS-SAL, IUHS-LPS. Body temperature was monitored in 30-min intervals and blood samples were obtained at 0, 1, 2, 3, 4, 6, and 8 h. Blood was analyzed for glucose, insulin, non-esterified fatty acids (NEFA), and cytokine concentrations. Body temperature increased (P < 0.01; 1.05°C) in LPS versus SAL pigs, regardless of in utero treatment. Glucose concentrations were reduced overall (P = 0.05; 5.9%) in IUHS versus IUTN pigs. Non-esterified fatty acid concentrations tended to be greater (P = 0.07; 143.4%) in IUHS-LPS pigs compared to all other treatments, and IUTN-LPS pigs tended to have greater circulating NEFA concentrations (127.4%) compared to IUTN-SAL and IUHS-SAL pigs. At 1 h, TNFα was increased (P = 0.01; 115.1%) in IUHS-LPS compared to IUTN-LPS pigs. Overall, IL-1β and IL-6 were greater (P < 0.04; 56.0 and 46.8%, respectively) in IUHS-LPS compared IUTN-LPS pigs. In summary, IUHS altered the postnatal immune and metabolic response of pigs during postnatal life, which has negative implications towards future disease susceptibility.